2019
DOI: 10.3390/pathogens9010033
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Binding, Cellular Cholesterol Content and Resealing Capacity Contribute to Epithelial Cell Damage Induced by Suilysin of Streptococcus suis

Abstract: Streptococcus (S.) suis is a major cause of economic losses in the pig industry worldwide and is an emerging zoonotic pathogen. One important virulence-associated factor is suilysin (SLY), a toxin that belongs to the family of cholesterol-dependent pore-forming cytolysins (CDC). However, the precise role of SLY in host–pathogen interactions is still unclear. Here, we investigated the susceptibility of different respiratory epithelial cells to SLY, including immortalized cell lines (HEp-2 and NPTr cells), which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 95 publications
(158 reference statements)
0
10
0
Order By: Relevance
“…SLY has been suggested to play a role in these early infection events [24][25][26]. Vötsch et al [27] investigated the susceptibility of different respiratory epithelial cells to SLY, including immortalized cell lines (HEp-2 and NPTr cells), which are frequently used in in vitro studies addressing S. suis virulence mechanisms, as well as primary porcine respiratory cells. It was observed that the human epithelial cell line HEp-2 is the most susceptible, whereas primary porcine epithelial cells were hardly affected by the toxin.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…SLY has been suggested to play a role in these early infection events [24][25][26]. Vötsch et al [27] investigated the susceptibility of different respiratory epithelial cells to SLY, including immortalized cell lines (HEp-2 and NPTr cells), which are frequently used in in vitro studies addressing S. suis virulence mechanisms, as well as primary porcine respiratory cells. It was observed that the human epithelial cell line HEp-2 is the most susceptible, whereas primary porcine epithelial cells were hardly affected by the toxin.…”
mentioning
confidence: 99%
“…The authors suggested that the choice of cells for in vitro studies on biological functions of virulence-associated factors, such as SLY, should be performed with models which more closely represent the in vivo situation than permanent cell lines. The study of Vötsch et al [27] also emphasized the importance of choosing the proper host species, as previous studies showed that SLY is a critical virulence factor in the mouse model, but not in pigs [28,29].…”
mentioning
confidence: 99%
“…Sly can lyse and damage a variety of cells and plays a vital role in SS2 invading the central system and destroying the BBB. In addition, Sly can induce the changes of host cytoskeleton (Lv et al, 2014) and the release of proinflammatory and immunomodulatory cytokines and chemokines, such as interlukin-6(IL-6), interlukin-8(IL-8), tumor necrosis factor-α(TNFα), and interlukin-8(IL-10) (Vötsch et al, 2019).…”
Section: Suilysin(sly)mentioning
confidence: 99%
“…S. suis produces a pore-forming cholesterol-dependent cytolysin (Suilysin) [ 41 , 42 , 43 ]. The different effects of this toxin on neutrophils are discussed [ 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%